Knowledge Acquisition, Knowledge Sharing, and Competitive Advantage in Culinary Business: The Mediating Role Of Innovation - Arisona, Dita; Andriani, Nurita (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2025)
The uneven success of duck culinary business in Bangkalan Regency needs to be analyzed with the aim of exploring the relationship between knowledge acquisition, knowledge sharing and competitive advantage with innovation as the mediating variable. The problem of duck culinary business in Bangkalan Regency on this paper was lack of knowledge management and to cause knowledge not upgraded. Researchers found that innovation is able to mediate the relationship between knowledge acquisition and competitive advantage, and innovation is able to mediate the relationship between knowledge sharing and competitive advantage. Data were collected from 64 duck culinary business owners in Bangkalan Regency with purposive sampling technique and data processing using SmartPLS 4. The results showed that there was a positive relationship between knowledge acquisition, knowledge sharing, and competitive advantage. Researched found that innovation was able to mediate the relationship between knowledge acquisition to competitive advantage , and innovation was able to mediate the relationship between knowledge sharing to competitive advantage. The implication of the research on the duck culinary business in Bangkalan Regency is that innovation is achieved when it has properly implemented knowledge acquisition and knowledge sharing, which will result in the duck culinary business to have a variety of potential duck preparations, have competitive selling prices and production costs, and have superior assets and human resources.